Study of Some Contribution in Operation Research - Nasim Akhtar; Prof. Mushtaque Khan (International Journal of Scientific Research in Science and Technology, 2024)
In this present paper, we studied about an operation research. The purpose of this paper is to first review some basic concepts operation research and goal programming. [1-13].
Keywords: Operation Research; Goal Programming; Game Theory